Finger Vein Authentication for Security Purpose - Racha Nikhil, Mohit Mirchandani, Dr.V.Kavitha (International Journal of Advanced Science and Technology, 2020)
Finger vein recognition is a form of biometric authentication which uses the image of patterns of the finger veins underneath the skin to identify and authenticate. Finger vein verification system is a kind of biometric system used to identify individuals and to check their identity. Finger Vein biometric system is a biometric authentication system that matches the vein pattern in a person’s finger to antecedent get information. This technology is currently in development or in use for producing many biometric systems, including MasterCard authentication, car security, attendance and time tracking for employees, network authentication, computer authentication, and ATM machines. The need for simple, helpful, and exceptionally secure authentication frameworks for protecting the ever-increasing amount of data stored on mobile devices. The private data are frequently ensured inside the kind of biometrics which utilizes human physiological or behavioral features for personal identification. The algorithm utilized in this project is SVM using MATHLAB language with a GUI interface.